Digital Transformation in Saudi Universities: Towards Sustainable Higher Education Aligned with Vision 2030 (The Arab Journal of Administration, 2026)
Globally, higher education is experiencing a rapid digital transformation fueled by technological progress and the growing adoption of artificial intelligence, compelling institutions to implement more flexible and sustainable systems for the knowledge economy. Within Saudi Arabia, Vision 2030 provides a strategic framework to advance this transformation, focusing on educational quality, digital infrastructure, and human capital development. Using an analytical desk research methodology based on recent literature, this study investigates the state of digital transformation in Saudi universities, examining their digital infrastructure, staff readiness, and the effectiveness of digital policies.Key findings reveal that digital transformation is a strategic imperative for sustainable education, involving the fundamental redesign of academic and administrative processes beyond simple technology adoption, in line with the Fourth Industrial Revolution and Vision 2030. This shift also promotes the SDGs by improving educational quality, expanding access, and lessening environmental impact. However, Saudi universities face significant challenges, including insufficient digital infrastructure, technical skill gaps, poor institutional integration, unclear policies, and difficulties in measuring transformation effectiveness.The findings highlight the critical need to upgrade infrastructure, develop human capital, and strengthen digital governance. The study recommends formulating comprehensive digital strategies, increasing infrastructure investment, and securing supportive policies from policymakers. It also suggests creating locally-tailored transformation models that reflect national identity and continuing applied research to assess impact and develop advanced evaluation metrics. These steps are vital to ensure the sustainability of this crucial path in response to future shifts and the demands of higher education in the Kingdom.